GROSS MARGIN ANALYSIS OF RASPBERRY PRODUCTION ON SELECTED FAMILY HOLDINGS IN SERBIA - Čanak, Stevan Miloš; Cvijanović, Vojin; Tomić, Vedran; Radišić, Robert (Economics of Agriculture, 2026)
This study analyzes the economic performance and riskexposure of raspberry production on selected family farmsin Serbia, identified by agricultural advisory services asregional leaders. Using gross margin calculations for theperiod 2020–2024, the results show that an average grossmargin was €14,546/ha or €1.57/kg. Strong year-to-yearfluctuations in gross margin were observed, ranging from€0.53/kg in 2023 to €2.97/kg in 2022. These variationswere primarily attributable to volatility in raspberry marketprices and escalating labor costs, which together accountedfor more than 80% of total variable expenses. Sensitivityanalysis indicated that most simulated scenarios yieldedpositive gross margins, suggesting a favorable outlookfor the selected Serbian farms. The findings underscorethe sector’s dependence on labor and unstable markets,highlighting the need for technological modernization,labor-saving innovations, and targeted institutional supportto sustain competitiveness in the global raspberry market.